Translating Filipino Slangs: Localization of Neologisms - Marvin Reyes (Scientia)
Slang or neologism can be considered as playful words that are being construed as something that defines the current generation’s set-up, culture, or background. It may also be considered the language of the current times but may differ depending on the projected culture to where it will be used. The study is about how, from a regular expression, a possible slang/neologism may be formed/constructed. The way that slang/neologism is being idealized as something new reflects how words are so dynamic and how, through their coinage, a word can signify a new meaning, a new perspective, and a new appreciation of culture and standards.